INFLUENCE OF CUSTOMIZATION STRATEGY AGAINST COMPANY PERFORMANCE WITH MANAGEMENT ACCOUNTING INFORMATION SYSTEM AS INTERVENING VARIABLE - Taty Sariwulan (International Journal of Contemporary Accounting, 2020)
This research aims to examine and analyze the influence of customization strategy on company performance with management accounting information systems as an intervening variable. In this research, the target population was the umrah travel agency registered at the Ministry of Religion in Bandung. Data obtained through the distribution of questionnaires addressed to the Director / Manager / Division Head of the company. Data analysis consists of descriptive and verification analysis. The results showed that the customization strategy, management accounting information systems and customization strategies that are intervening by management accounting information system have a positive effect on company performance. Based on the evaluation of structural models, the customization strategy in intervening management accounting system information gives a positive effect better than the direct effect with value 0.216. Management accounting information systems is needed to overcome uncertainties in determining and assessing the causal relationships that occur due to product customization that is undergoing constant changes to the product design and process. This research is also expected to contribute conceptually to the company in determining further policies regarding the performance of a company to be more effective in its implementation.